Corporate Social Responsibility inside the best valued companies within the labor market - Ferreiro-Seoane, Francisco Jesús; Corchuelo Martínez-Azúa, Beatriz (Cuadernos de Administración, 2019)
Annually, the magazine Revista Actualidad Económica (RAE) publishes a ranking of the 100 most attractive companies to work for, in Spain. Using this database for the period 2013-2018, the aim of this study is to analyze the assessment of the CSR and compare it with the total valuation of the companies, based on a series of variables such as the territorial location of the enterprises, their nationality, their main activity sector, their size and contribution, which allows us to know the profile of these organizations. The techniques of analysis used are: statistical analysis, comparison of medians of independent samples with Levene test and econometric analysis. It is a novel work since there are no previous studies that involve a quantitative analysis of the organizations within the main positions of the rankings. The most relevant results prove the existence of a positive relationship between the largest companies and those listed on the stock exchange with the values obtained by the CSR and the total valuation. Furthermore, the Anglo-Saxon companies have a significant valuation overall if we compare it with the Mediterranean companies; however, regarding CSR, they obtain similar values. The profile obtained for the most outstanding companies in CSR and global valuation corresponds, almost completely, to large companies listed on the stock market, inside the energy and financial sector, mainly Anglo-Saxon companies located in the capital of Spain. Future researches should assure whether new results are obtained by considering additional variables or not.